Similar temperature sensitivity of soil mineral-associated organic carbon regardless of age. (September 2019) - Karhu, Kristiina; Hilasvuori, Emmi; Järvenpää, Marko; Arppe, Laura; Christensen, Bent T.; Fritze, Hannu; Kulmala, Liisa; Oinonen, Markku; Pitkänen, Juha-Matti; Vanhala, Pekka; Heinonsalo, Jussi; Liski, Jari
Abstract: Most of the carbon (C) stored in temperate arable soils is present in organic matter (OM) intimately associated with soil minerals and with slow turnover rates. The sensitivity of mineral-associated OM to changes in temperature is crucial for reliable predictions of the response of soil C turnover to global warming and the associated flux of carbon dioxide (CO2 ) from the soil to the atmosphere. We studied the temperature sensitivity of C in <63 μm fractions rich in mineral-associated organic matter (MOM) and of C in >63 μm fractions rich in particulate organic matter (POM). The fractions were isolated by physical separation of two light-textured arable soils where the C4-plant silage maize had replaced C3-crops 25 years ago. Differences in 13 C abundance allowed for calculation of the age of C in the soil-size fractions (old C, C3–C > 25 years; recent C, C4–C < 25 years). We incubated bulk soils (<2 mm) and size fractions sequentially at 6, 18, 26 and 34 °C (ramping up and down the temperature scale) and calculated the temperature sensitivity of old and recent C from 12 CO2 and 13 CO2 evolution rates. The temperature sensitivity was similar or slightly higher for POM than for MOM. Within the POM fraction, old C3–C was more sensitive to changes in temperature than recent C4–C. For the MOM fraction, the temperature sensitivity was unrelated to the age of C. Quantitative PCR analysis indicated that the proportions of bacteria, archaea and fungi did not change during incubation. Our results suggest that while OM stabilizing mechanisms affect the temperature sensitivity of soil C, temperature sensitivity appears unrelated to the age of mineral-associated OM. Highlights: Temperature sensitivity of mineral-associated SOM was not related to its age. Temperature sensitivity of POM fraction was similar or slightly higher than MOM. Within the POM fraction, old C was more sensitive to temperature than recent C.